BORON ISOTOPIC COMPOSITION OF ATMOSPHERIC PRECIPITATIONS AND LIQUID-VAPOUR FRACTIONATIONS - Rose-Koga E.F.; Sheppard S.M.F.; Chaussidon M.; Carignan J. (My University, 2006)
Boron isotope compositions (?11B) and B concentrations of rains and snows were studied in order to characterize the sources and fractionation processes during the boron atmospheric cycle. The 11B/10B ratios of instantaneous and cumulative rains and snows from coastal and continental sites show a large range of variations, from -1.5 ? 0.4 to +26.0 ? 0.5? and from -10.2 ? 0.5 to + 34.4 ? 0.2?, respectively. Boron concentrations in rains and snows vary between 0.1 and 3.0 ppb. All these precipitation samples are enriched in 10B compared to the ocean value (?11B = +39.5?). An empirical rain-vapour isotopic fractionation of +31? is estimated from three largely independent methods. The deduced seawater-vapour fractionation is +25.5?, with the difference between the rain and seawater fractionations principally reflecting changes in the speciation of boron in the liquid with ?100% B(OH)3 present in precipitations. A boron meteoric water line, ?D = 2.6?11B - 133, is proposed which describes the relationship between ?D and ?11B in many, but not all, precipitations. Boron isotopic compositions of precipitations can be related to that of the seawater reservoir by the seawater-vapour fractionation and one or more of (1) the rain-vapour isotopic fractionation, (2) evolution of the ?11B value of the atmospheric vapour reservoir via condensation-precipitation processes (Rayleigh distillation process), (3) any contribution of vapour from the evaporation of seawater aerosols, and (4) any contribution from particulate matter, principally sea salt, continental dust and, perhaps more regionally, anthropogenic sources (burning of biomass and fossil fuels). From the ?11B values of continental precipitations, a sea salt contribution cannot be more than a percent or so of the total B in precipitation over these areas. ? 2006 Elsevier Inc. All rights reserved.
Keywords: ATMOSPHERIC DEPOSITION; BORON; ISOTOPIC COMPOSITION; RAINFALL